The communication experience of mothers of street children: A phenomenological study - Tayo, Yanti; Nursanti, Siti (Universitas Bunda Mulia, 2023)
There are different types of uniqueness and diversity of mothers who can be an option for women who, in addition to carrying out their duties as mothers, choose to carry out other activities such as working mothers, mothers who become politicians, and mothers who have street children, as in the research conducted. The purpose of this research is to find out how the mother's communication experience is on the streets. This study was carried out using qualitative research methods and Alfred Schutz's phenomenological approach. Researchers take steps that are deemed necessary in order to explore and comprehend the experiences of street children's mothers and their points of view. This study included 14 informants, including 10 key informants and 4 additional informants. The findings of this study are the experiences of street children's mothers while accompanying their children to work on the streets, as well as the actions they receive from other people as a result of the street children's mothers' acts of communication. Mothers of street children have both pleasant and unpleasant communication experiences; As for the unpleasant experiences that were obtained, among others, being considered an irresponsible mother for allowing her child to be on the streets even though she knew that the streets were very dangerous for herself and her child. Meanwhile, a pleasant experience gained by a mother of street children is the closeness she feels with her child, considering that mothers of street children will be with their children longer than other mothers, mothers of street children can discuss many things with their children, understand children better and discuss what they will do and where they will go each day. From this communication experience, mothers interpret the meaning of children as reinforcement in the life they live and children as helpers who will bring mothers of street children to a better life.